The Indonesian verbal suffix "-nya"; Nominalization or subordination? - Grangé, Philippe (Wacana, Journal of the Humanities of Indonesia, 2015)
The suffix nya is one of the most frequent and polysemic suffixes in Indonesian. It can provide definite determination and topicalization. The "Verb nya", which often appears in a topicalized subject Noun Phrase (NP), is generally labelled as a deverbal noun. Nevertheless, many syntactic constraints set it apart from Indonesian deverbal nouns. "Verb nya" must be complemented by a NP, which can easily be reconstructed as a former subject: a sentence is topicalized and thus becomes a noun clause, generally the subject of the main clause Verb Phrase (VP). I argue that "Verb nya" is a subordinate noun clause, almost always conveying causality. This causal noun clause, an innovation in formal written Indonesian (especially in the media), seems to fill a "gap": the impossibility of beginning a sentence with a subordinating morpheme ('that', 'because').